2016
DOI: 10.1111/mcn.12385
|View full text |Cite
|
Sign up to set email alerts
|

Impact of integrated child development scheme on child malnutrition in West Bengal, India

Abstract: With child malnutrition detected as a persistent problem in most of the developing countries, public policy has been directed towards offering community-based supplementary feeding provision and nutritional information to caregivers. India, being no exception, has initiated these programs as early as 1970s under integrated child development scheme. Using propensity score matching technique on primary data of 390 households in two districts of West Bengal, an Eastern state in India, the study finds that impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…The sum of this figure is therefore greater than the total 368 included papers. Of the papers that look at 'adequacy of resources', a majority (N=45 times) explore system level inputs such as percentage of AWCs housed in pucca (permanent) buildings (Gupta et al 2013); availability of counselling material at AWCs (Saxena et al 2015); presence of electricity (Singh and Masters 2016;Avula et al 2015); AWCs functioning for the requisite number of hours (Dutta and Ghosh 2017;Avula et al 2015); or health worker presence at the AWC (Das et al 2018) as reported by programme participants (Pati et al 2016).…”
Section: Programme Levelmentioning
confidence: 99%
“…The sum of this figure is therefore greater than the total 368 included papers. Of the papers that look at 'adequacy of resources', a majority (N=45 times) explore system level inputs such as percentage of AWCs housed in pucca (permanent) buildings (Gupta et al 2013); availability of counselling material at AWCs (Saxena et al 2015); presence of electricity (Singh and Masters 2016;Avula et al 2015); AWCs functioning for the requisite number of hours (Dutta and Ghosh 2017;Avula et al 2015); or health worker presence at the AWC (Das et al 2018) as reported by programme participants (Pati et al 2016).…”
Section: Programme Levelmentioning
confidence: 99%
“…Implementation of ECE in Anganwadi centres is variable across the state, with only 60-85% of centres in each district providing this service [30,[35][36][37]. A crosssectional study found that where provided, the duration of ECE activities averaged at only 60 min, below the 120 min prescribed in policy.…”
Section: Integrated Child Development Scheme (Icds)mentioning
confidence: 99%
“…Consequently the presumed more satisfying dietary diversity resulting from the AWC/ICDS meal may be misleading, due to diminished quantities of key foods being utilized by the index child alone. Further irregular program delivery or unstable distribution of egg is reported, as possible reason why the ICDS remained unsuccessful in reducing stunting rates [68]. Similarly obtained qualitative information in two Centers in the project area already indicated that the provided full egg is sometimes replaced by half of that portion, and amounts of oil, vegetables, potatoes and soy allocated per child varied across the Centers showing several limitations in the performance of the ICDS authorities.…”
Section: Complementary Feeding Practicesmentioning
confidence: 99%
“…The nutritional status may not be used as indicator of ICDS program performance [70], but still recent program evaluations reported the ICDS program -launched in 1975, having had a positive impact on normal children and those suffering from a mild form of malnutrition, whereas there was no impact on children suffering from moderate or severe forms of malnutrition [71]. According to Dutta et al increased supervision but also intensified complementary nutritional education will maximize the impact of ICDS services on child growth [68]. AWC worker may be further encouraged and made aware of the importance of their work to raise more awareness about the necessity of proper nutrition for the whole family.…”
Section: Complementary Feeding Practicesmentioning
confidence: 99%